The Use of Bilingual Educational Booklet as the Implementation of the Tagline ‘Sinau Maring Alam, Ora Bakal Nggawe Kowe Gela’ in Taman Botani Baturraden - Nadya Salma (Jurnal Vokasia, 2024)
This research is entitled "Creating Bilingual Educational Booklet as the Implementation of the Tagline 'Sinau Maring Alam, Ora Bakal Nggawe Kowe Gela' in Taman Botani Baturraden". The main purpose of the job training is to create a bilingual educational booklet in Taman Botani Baturraden. This booklet was created to implement the tagline of Taman Botani Baturraden, that is 'Sinau Maring Alam, Ora Bakal Nggawe Kowe Gela', which means learning from nature will not make you disappointed. Moreover, the learning media of Taman Botani Baturraden was unavailable before. The creation of this booklet could help visitors to know the plants in Taman Botani Baturraden, which means that this booklet aligned with the tagline and educational theme brought by Taman Botani Baturraden. In making the booklet, the author used four methods, there were observation, documentation, staff interview, and design making. The observation was carried out by the author to observe and obtain data on plants in Taman Botani Baturraden. Documentation was carried out to get the best photos of plants as visual support in the booklet. For the staff interview stage, the author found more information about plants in the booklet. Then, the last stage is making a booklet design using the basic green color as a representation of plants in Taman Botani Baturraden. During the booklet making process, the author encountered several obstacles in the process. The obstacle is in determining the color and font. This is because Taman Botani Baturraden did not have a specific color palette and fonts for their products, so the author studied color and font theory again to determine it. Then, not all plants were in bloom, so the author could not document the plants thoroughly. The solution to these obstacles was to discuss with job training supervisors and supervisors in Taman Botani Baturraden.